2012
DOI: 10.2478/s11696-012-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ag-doping of nanosized FeMgO system on its structural, surface, spectral, and catalytic properties

Abstract: The effects of Ag-doping on the physico-chemical, spectral, surface, and catalytic properties of the FeMgO system with various Fe2O3 loadings were investigated. The dopant (Ag) molar ratio varied between 0.01 % and 0.05 %. The techniques employed for characterisation of catalysts were TG/DTG, XRD, ESR, N2 adsorption at −196°C, and catalytic decomposition of H2O2 at 25–35°C. The results obtained revealed that the investigated catalysts consisted of nanosized MgO as the major phase, apart from the MgFe2O4 and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The sample was prepared by impregnation of a known amount of finely powdered magnesium hydroxide, which was prepared previously [26], with an aqueous solution containing a known amount of iron nitrate dissolved in the least amount of bi-distilled water necessary to make a paste. The resulting paste was dried at 110°C and then calcined at 500°C for 4 h. The composition of the sample prepared was nominated as FeMgO IM .…”
Section: Wet Impregnation Methods (Im)mentioning
confidence: 99%
See 1 more Smart Citation
“…The sample was prepared by impregnation of a known amount of finely powdered magnesium hydroxide, which was prepared previously [26], with an aqueous solution containing a known amount of iron nitrate dissolved in the least amount of bi-distilled water necessary to make a paste. The resulting paste was dried at 110°C and then calcined at 500°C for 4 h. The composition of the sample prepared was nominated as FeMgO IM .…”
Section: Wet Impregnation Methods (Im)mentioning
confidence: 99%
“…1(a) and Table 1. It was clearly noticed that the XRD diffractogram of the FeMgO IM sample contained peaks due to MgO phase (periclase) (JCPDS 4-829) with a moderate degree of ordering [26]. The XRD diffractogram of FeMgO Co sample contained peaks of MgO phase with very low degree of crystallinity.…”
Section: Adsorbent Characterization: Xrdmentioning
confidence: 97%
“…The surface texture of FeMgO catalysts were previously investigated by two of authors [11] and the most important results were reported as followings: i) the addition of a small amount of Fe2O3 to the MgO support followed by calcination at 500 o C resulted in an increase in SBET of hematite. The increase in the Fe2O3 molar content to 10 mol% is accompanied by a limited decrease in SBET.…”
Section: Influence Of Cu 2+ -Doped Femgo Nanomaterials …mentioning
confidence: 99%
“…Therefore, supporting iron oxide usually results in modification of its textural, structural, and catalytic properties [4]. It is known that the activity and selectivity of a large variety of catalysts can be modified by loading them on a fine support and doping them with certain foreign oxides [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Fe 2 O 3 /MgO nano-composite prepared by impregnation, coprecipitation and hydrothermal have biomedical, catalytic and magnetic applications [4,11]. It was reported that doping the catalytic system with certain foreign oxides is accompanied by significant modifications in its thermal stability, surface, and catalytic properties [6]. It has been reported that doping the magnetite with chromium ions has a remarkable effect on its crystallinity, surface area, porosity and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%